From growth to great - Chowdhury, Rumman (IEEE, 2018)
In this course we will examine how the growth of Artificial Intelligence is aligned with responsible business practice, and will understand the need for, and principles of, Agile Governance. Next we will review how ethical considerations tie into the ongoing manufacture, implementation and policy regarding AI/AS and finally we'll discover how standards for Ethical AI/AS can enhance growth